PENGEMBANGAN MEDIA PEMBELAJARAN SIGAP TERHADAP HASIL BELAJAR PEMAHAMAN KONSEP IPA - A. Nur Azizah Asfin; Ferdiansyah, Handy; Takdir, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop the SIGAP learning media and test its validity, practicality, and effectiveness on students' conceptual understanding of science concepts in seventh-grade students at the UPT SMP Negeri 1 Panca Rijang. This study employed a mixed methods approach with an exploratory sequential design and a Research and Development (R&D) methodology that applied the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Qualitative data were obtained through observation and interviews, while quantitative data were obtained through questionnaires, tests, and validation sheets. The study subjects consisted of two validators (a material expert and a media expert), one science teacher, and 109 students as a sample of 164 students. The effectiveness test used a one-group pretest-posttest design. The results showed that the SIGAP learning media was categorized as "very valid," with a percentage of 90–100% based on validator assessments. Its practicality was also categorized as "very practical," with a percentage of 90–100% based on teacher and student responses. The results of the normality test indicated that the data were not normally distributed, so the analysis continued using the Wilcoxon Signed Ranks Test. The Wilcoxon test results showed an Asymp. Sig. (2-tailed) value of 0.000 < 0.05 with a Z-value of -9.061, indicating a significant difference between the pre-test and post-test scores. The N-Gain analysis showed an average of 0.8649 (86.4861%), categorized as high. Based on these results, it can be concluded that the SIGAP learning media developed is highly valid, practical, and effective in improving students' conceptual understanding of science in grade VII at UPT SMP Negeri 1 Panca Rijang.